PENGARUH LOKASI, KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA PASAR TRADISIONAL ( Studi Kasus Pada Pasar Tradisional di Kabupaten Tulang Bawang Barat.) - Tara Ismiah; Defrizal Defrizal (Jurnal Ilmiah Akuntansi Rahmaniyah, 2023)
The research conducted ascertains how location, product quality, and price affect consumer satisfaction in traditional markets in West Tulang Bawang Regency. To collect data for this study, questionnaires or a number of statements were presented to a total of 100 respondents. Respondents were taken from traditional market visitors in Tulang Bawang Barat Regency. Data processing uses SPSS version 25. The results of the research location do not have a significant effect on customer satisfaction, product quality has a significant effect on customer satisfaction and price also has a significant effect on customer satisfaction. Simultaneously significant effect on customer satisfaction.